Cavin-3 knockout mice show that cavin-3 is not essential for caveolae formation, for maintenance of body composition, or for glucose tolerance. - Libin Liu; Carsten G Hansen; Brian J Honeyman; Benjamin J Nichols; Paul F Pilch (PLoS ONE)
The cavins are a family of proteins associated with caveolae, cavin-1, -2 and -3 being widely expressed while cavin-4 is restricted to striated muscle. Deletion of cavin-1 results in phenotypes including metabolic changes consistent with adipocyte dysfunction, and caveolae are completely absent. Deletion of cavin-2 causes tissue-specific loss of caveolae. The consequences of cavin-3 deletion are less clear, as there are divergent data on the abundance of caveolae in cavin-3 null mice. Here we examine the consequences of cavin-3 deficiency in vivo by making cavin-3 knockout mice. We find that loss of cavin-3 has minimal or no effects on the levels of other caveolar proteins, does not appear to play a major role in formation of protein complexes important for caveolar morphogenesis, and has no significant effect on caveolae abundance. Cavin-3 null mice have the same body weight and fat mass as wild type animals at ages 8 through 30 weeks on both normal chow and high fat diets. Likewise, the two mouse strains exhibit identical glucose tolerance tests on both diets. Microarray analysis from adipose tissue shows that the changes in mRNA expression between cavin-3 null and wild type mouse are minimal. We conclude that cavin-3 is not absolutely required for making caveolae, and suggest that the mechanistic link between cavin-3 and metabolic regulation remains uncertain.